Evidence - Heydon, J. D. (Butterworths, 1996)
This collection of cases and materials is intended for use on all university courses and in preparing for professional examinations. English cases and statutes form the basis of the book but, American, Australian and Scots cases have been included where relevant. Includes the provisions of the Criminal Justice Act 1991, Criminal Justice Act 1993 and the impact of the Criminal Justice and Public Order Act 1994